Let's start with a simple one-step equation:
Original Equation:
- \( x + 5 = 12 \)
Equations Equivalent to the Original: 2. \( x = 12 - 5 \) 3. \( x = 7 \)
Why These Equations Are Equivalent:
To prove that all three equations are equivalent, we can manipulate and derive each equation from the others.
-
From Original Equation to First Equivalent:
- Start with the original equation: \( x + 5 = 12 \)
- Subtract 5 from both sides: \[ x + 5 - 5 = 12 - 5 \]
- Simplifying yields: \[ x = 12 - 5 \]
-
From Original Equation to Second Equivalent:
- Using the original equation \( x + 5 = 12 \):
- We already derived \( x = 12 - 5 \).
- Now, calculate \( 12 - 5 \): \[ 12 - 5 = 7 \]
- This gives us: \[ x = 7 \]
-
From First Equivalent to Second Equivalent:
- Starting with \( x = 12 - 5 \):
- Simplifying the right side gives us: \[ x = 7 \]
Thus, we have shown that we can derive each equation from one another through basic algebraic manipulations, proving that all three equations are equivalent. Each equation represents the same solution for \( x \).